Alien plant invasion hotspots and invasion debt in European woodlands. (19th April 2021) - Wagner, Viktoria; Večeřa, Martin; Jiménez‐Alfaro, Borja; Pergl, Jan; Lenoir, Jonathan; Svenning, Jens‐Christian; Pyšek, Petr; Agrillo, Emiliano; Biurrun, Idoia; Campos, Juan Antonio; Ewald, Jörg; Fernández‐González, Federico; et al.
Abstract: Questions: European woodlands harbor at least 386 alien plant species but the factors driving local invasions remain unknown. By using a large vegetation‐plot database, we asked how local richness and abundance of alien species vary by regions, elevation, climate, soil properties, human disturbance, and habitat types. Location: Western, central and southern Europe. Methods: We linked consolidated data from the European Vegetation Archive (16, 211 plots) to a habitat classification scheme, climate, soil properties and human disturbance variables. In addition, we used 250 km × 250 km regional grid cells to test whether local patterns differ among regions. We used generalized additive models (GAMs) and quantile GAMs to explore how relative alien species richness and the sum of alien species covers per plot relate to predictors. Random Forest analyses (RFs) were employed to assess the importance of individual predictors that were not multicollinear. Results: Relative alien species richness and the sum of alien species covers varied across regions and habitat types, with effects being more pronounced at the maximum rather than average responses. Both response variables declined with increasing elevation and distance to the nearest road or railroad and increased with the amount of sealed soil. Maxima in fitted functions matched plots from regional invasion hotspots in northwestern and central Europe. RFs accounted for 39.6% and 20.9% of the total variation in relative alien species richness and the sum of alien species covers, respectively, with region and habitat being the most important variables. Conclusions: The importance of maximum response quantiles and the prevalence of regional hotspots point to invasion debt in European woodlands. As alien plants expand further, their species richness and abundance in woodlands will be likely driven by the shared effects of the introduction and planting history, differences in the invaded habitat types, and dispersal corridors. Abstract : Using a large vegetation‐plot data set from the European Vegetation Archive, we explored the relationship between the levels of alien plant invasion and environmental variables in European woodlands. Habitat types and regions emerged as the most important predictors, with the latter pointing to regional hotspots of local alien plant invasion and regional invasion debt in woodlands across Europe.